Paths in the eastern Congo rainforest: Vernacular histories, colonial interpretations and linguistic data on the settlement of the lower Lualaba - Birgit Ricquier; Laurent Nieblas Ramirez; Alexandre Livingstone Smith; Shingo Takamura; David Kopa Wa Kopa; Daou Véronique Joiris (Afriques)
The early history of the lower Lualaba, the region between Kisangani and Lowa, is mostly known from Moeller’s Les grandes lignes des migrations des Bantous de la Province Orientale du Congo belge (1936). This work is largely based on vernacular histories collected and reinterpreted by various colonial administrators. Here, we present recently recorded vernacular histories and a reanalysis of relevant documents from the AIMO colonial archives. The combination of these sources allows for sketching a cultural chronostratigraphy of the region. Moreover, the proposed paths and cultural exchanges display striking similarities to the history of the concerned languages. We conclude that the current inhabitants of the region arrived in the late precolonial period, after which cultural admixture took place, especially between Lengola, Mbole and Wagenya-Mokpa-Metoko. Vernacular histories and linguistic evidence seem to suggest that the region was sparsely populated before, except for the Falls area, which was already buzzing with activity before the Wagenya occupation in the early 19th century. The two types of evidence do not offer access to earlier periods, which can be revealed only by future archaeological research.